Структурный синтез гетерогенной оптической телекоммуникационной сети xWDM - Агеев, Д. В.; Хайдара Абдалла (Проблеми телекомунікацій, 2012)
Heterogeneous optical network with ring topology on backbone segment structural synthesis method was proposed, which use model of elastic network. Application of this model has reduced the time required to solve the problem.
Keywords: оптическая сеть; кольцевая топология; эластичная сеть; граф; световой путь